Study guides

☆☆

Q: 2x3 plus 2x2 - 12x

Write your answer...

Submit

Still have questions?

Related questions

-2x3 + 2x2 + 12x =(-2x) (x2 - x - 6) =(-2x) (x+2) (x-3)

whats the answer for -2x^3+2^2+12x

(-2x3 - 2x2 + 12x) = -2x (x2 + x - 6) = -2x (x + 3) (x - 2)

I assume your problem is: -2x3-2x2+12x-2x(x2-x-6)-2x(x-3)(x+2)

-2x3 + 2x2 + 12x = -2x(x2 - x - 6) = -2x(x2 + 2x - 3x - 6) = -2x[ x(x + 2) - 3(x + 2) ] = -2x(x - 3)(x + 2)

-2x3 - 2x2 + 12x = -2x(x2 + x - 6) = -2x(x2 - 2x + 3x - 6) = -2x[ x(x - 2) + 3(x - 2) ] = -2x(x + 3)(x - 2)

2x( x2 + x - 6) = 2x (x + 3)(x - 2)

Yes. 2x3 - 11x2 + 12x + 9 = (x - 3)(2x2 - 5x - 3) = (x - 3)(2x2 - 6x + x - 3) = (x - 3)(2x + 1)(x - 3) = (2x + 1)(x - 3)2

-2x(x + 3)(x - 2)

Rearrange: 4x5 + 6x2 + 6x3 + 9 Group: 2x2 (2x3 + 3) + 3 (2x3 + 3) Simplify to get your answer: (2x2 + 3) (2x3 + 3)

-2x3-2x2+12x (-2)(x3+x2-6x) (-2x)(x2+x-6) (-2x)(x2+3x-2x-6) (-2x)((x)(x+3)-2(x+3)) (-2x)((x-2)(x+3)

There is no rational factorisation to this expression.

People also asked